Pengaruh Aplikasi Youtube Dalam Meningkatkan Keaktifan Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen Kelas X SMK YP Cerdas Mandiri - Tampubolon, Samto Rediwan; Siregar, Nurliani; Bangun, Bangun (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to analyze the effect of using the YouTube application on students' learning activeness in Christian Religious Education subjects in grade X at SMK YP Cerdas Mandiri. This research uses a quantitative method with descriptive and inferential statistical analysis. Descriptive statistics are used to describe the research data, while inferential statistics are used to test hypotheses and examine the relationships between variables. The results of the study show that the use of the YouTube application has a significant effect on students' learning activeness. Based on the correlation test, a correlation coefficient value of 0.3 was obtained, indicating a strong relationship between the use of YouTube and students' learning activeness. The t-test showed a t_calculated value of 2.67, which is greater than the t_table value of 1.69, meaning this relationship is significant. The coefficient of determination of 20.3% indicates that the use of YouTube contributes to 20.3% of students' learning activeness. Additionally, a simple linear regression analysis revealed the regression equation Y = 0.411 + 0.3X, meaning that each increase in YouTube usage will increase students' learning activeness. The independence and linearity tests of the regression also support the conclusion that the variables in this study are linear and independent. Thus, this study concludes that the YouTube application can significantly enhance students' learning activeness.